Multiple origins and circular structures in replicating T5 bacteriophage DNA. - Bourguignon, G J (1976)
Replicating T5 phage DNA was gently isolated using NaI density gradient centrifugation and examined by electron microscopy. At the beginning of phage DNA synthesis, linear unit-length T5 DNA molecules containing from one to four replicating "eye-loops" were consistently observed. Replication in these molecules was found to proceed bidirectionally from multiple, internal origins. A primary origin of replication is located near the center of the T5 genome, which does not coincide with the location of any of the nicks (single-strand breaks) found in mature T5 DNA. The initiation of replication at the various origins within an individual molecule does not appear to follow any definite temporal sequence. At later times in the infection, we have observed a significant number of circular T5 DNA molecules-both replicating and nonreplicating-whose average circumference is approximately the length of mature T5 DNA minus the terminal redundancy. The replicating circular molecules appear to be either in a theta configuration, a sigma configuration with the tails all being less than the length of the circle, or a combination of theta and sigma forms.